Anionic azo dyes and their removal from textile wastewater through adsorption by various adsorbents: a critical review - Strebel, Annika; Behringer, Martin; Hilbig, Harald; Machner, Alisa; Helmreich, Brigitte (Frontiers in Environmental Engineering, 2024)
The review aimed to identify differences and similarities in the adsorption process of five azo dyes (congo red (CR), reactive black 5 (RB5), methyl orange (MO), orange II (OII), and methyl red (MR)) on natural materials, biosorbents, industrial and agricultural waste, or biomass, which are alternatives of costly activated carbon and are locally available. The azo dyes were characterized and compared based on their molecular structure and weight, water solubility, acid dissociation constant, n-octanol-water partition coefficient, and maximum absorbance. RB5 and CR are diazo dyes, whereas MO, OII, and MR are mono-azo dyes. MO, OII, and MR are anionic acid dyes, RB5 is an anionic reactive dye, and CR is an anionic direct dye. CR, RB5, MR, and OII molecules contain one or more sulfonate functional group(s), but MR does not. We performed a literature review based on the following parameters: initial dye concentration, adsorbent dosage, pH, temperature, isotherm, kinetic models, thermodynamic parameters, and synergetic or competitive interactions. The azo dyes tended to adsorb best in an acidic medium and at higher temperatures. The initial dye concentration and adsorbent dosage studies indicated the importance of using an appropriate amount of adsorbent dosage for an effective removal. The studies tended to follow the Langmuir isotherm and kinetic pseudo-second-order model. Most adsorption processes were endothermic and spontaneous, leading to an increase in randomness at the solid-liquid interface. These results indicate similarities between the adsorption process of the five azo dyes. Relevant adsorption mechanisms in azo dye adsorption processes were assumed to be electrostatic forces, hydrogen bonding, and π–π interactions, among others. Nevertheless, the focus of the studies lies more on the development and characterization of adsorbent materials, not on the study of influences from the matrix "industrial wastewater". Therefore, more research is needed to develop adsorption units for application in textile industries.